Distinct regulatory machineries underlying divergent chromatin landscapes distinguish innate lymphoid cells from T helper cells - Zhang, Yime; Hu, Luni; Ren, Guanqun; Zeng, Yanyu; Zhao, Xingyu; Zhong, Chao (Frontiers in Immunology, 2023)
Innate lymphoid cells (ILCs), as the innate counterpart of CD4 + T helper (Th) cells, play crucial roles in maintaining tissue homeostasis. While the ILC subsets and their corresponding Th subsets demonstrate significant similarities in core programming related to effector function and regulatory mechanisms, their principal distinctions, given their innate and adaptive lymphocyte nature, remain largely unknown. In this study, we have employed an integrative analysis of 294 bulk RNA-sequencing results across all ILC and Th subsets, using scRNA-seq algorithms. Consequently, we identify two genesets that predominantly differentiate ILCs from Th cells, as well as three genesets that distinguish various immune responses. Further, through chromatin accessibility analysis, we find ILC geneset tends to rely on specific transcriptional regulation at promoter regions compared to Th geneset. Additionally, we observe that ILCs and Th cells are under differential transcriptional regulation. For example, ILC are under stronger regulation by multiple transcription factors, including RORα, GATA3 and NF-κB. Otherwise, Th cells are under stronger regulation by AP-1. Thus, our findings suggest that, despite the acknowledged similarities in effector functions between ILC subsets and corresponding Th subsets, the underlying regulatory machineries still exhibit substantial distinctions. These insights provide a comprehensive understanding of the unique roles played by each cell type during immune responses.